NR4A3 fusions characterize a distinctive peritoneal mesothelial neoplasm of uncertain biological potential with pure adenomatoid/microcystic morphology - Agaimy, Abbas; Brcic, Luka; Briski, Laurence M; Hung, Yin P; Michal, Michael; Michal, Michal; Nielsen, G Petur; Stoehr, Robert; Rosenberg, Andrew E (Genes, chromosomes & cancer, 2023)
A focal adenomatoid-microcystic pattern is not uncommon in peritoneal mesothelioma, but tumors composed almost exclusively of this pattern are distinctly rare and have not been well characterized. A small subset of mesotheliomas (mostly in children and young adults) are characterized by gene fusions including EWSR1/FUS::ATF1, EWSR1::YY1, and NTRK and ALK rearrangements, and often have epithelioid morphology. Herein, we describe five peritoneal mesothelial neoplasms (identified via molecular screening of seven histologically similar tumors) that are pure adenomatoid/microcystic in morphology and unified by the presence of an NR4A3 fusion. Patients were three males and two females aged 31-70 years (median, 40 years). Three presented with multifocal/diffuse and two with a localized disease. The size of the individual lesions ranged from 1.5 to 8 cm (median, 4.7). The unifocal lesions originated in the small bowel mesentery and the mesosigmoid. Treatment included surgery, either alone (three) or combined with hyperthermic intraperitoneal chemotherapy (two), and neoadjuvant or adjuvant chemotherapy (one case each). At the last follow-up (6-13 months), all five patients were alive and disease-free. All tumors were morphologically similar, characterized by extensive sieve-like microcystic growth with bland-looking flattened cells lining variably sized microcystic spaces and lacked a conventional epithelioid or sarcomatoid component. Immunohistochemistry confirmed mesothelial differentiation, but most cases showed limited expression of D2-40 and calretinin. Targeted RNA sequencing revealed an NR4A3 fusion (fusion partners were EWSR1 in three cases and CITED2 and NIPBL in one case each). The nosology and behavior of this morphomolecularly defined novel peritoneal mesothelial neoplasm of uncertain biological potential and its distinction from adenomatoid variants of conventional mesothelioma merit further delineation as more cases become recognized.
Keywords: Gene Fusion; DNA-Binding Proteins; Humans; receptory thyreoidních hormonů; lidé středního věku; DNA vazebné proteiny; Biomarkers, Tumor; mezenterium; Female; Aged; dospělí; Receptors, Thyroid Hormone; senioři; lidé; Cell Cycle Proteins; represorové proteiny; gene fusion; nádorové biomarkery; Adult; Trans-Activators; Receptors, Steroid; Repressor Proteins; ženské pohlaví; microcystic; Male; Mesentery; Middle Aged; trans-aktivátory; steroidní receptory; mezoteliom; Mesothelioma; proteiny buněčného cyklu; adenom; Adenoma; EWSR1; fúze genů; peritoneální nádory; mužské pohlaví; Peritoneal Neoplasms; adenomatoid tumor; peritoneal mesothelioma; NR4A3